2018
DOI: 10.1061/(asce)co.1943-7862.0001406
|View full text |Cite
|
Sign up to set email alerts
|

Construction Workers’ Well-Being: What Leads to Depression, Anxiety, and Stress?

Abstract: Work-related stress is an important issue in any industry, particularly for construction workers where stressful environments are frequently encountered. Critical questions are therefore: what are the primary stressors in the construction workplace ; and what are the relationships between the strain effect of psychological distress and the countermeasures and coping mechanisms used by construction workers? The first question was addressed using Qmethodology survey with 18 participants. The results show that ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 62 publications
4
82
2
2
Order By: Relevance
“…Nature of tasks, lack of personal and family time, increase in the cost of living, and fears about job security act as powerful stressors. Coping strategies including acceptance, self-blame, substance abuse, and disengagement are associated with higher levels of psychological distress [ 26 ]. Another study identified missing special events (86%), relationship problems with partners (68%), financial stress (62%), shift rosters (62%), and social isolation (60%) as stressors among mining and construction workers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nature of tasks, lack of personal and family time, increase in the cost of living, and fears about job security act as powerful stressors. Coping strategies including acceptance, self-blame, substance abuse, and disengagement are associated with higher levels of psychological distress [ 26 ]. Another study identified missing special events (86%), relationship problems with partners (68%), financial stress (62%), shift rosters (62%), and social isolation (60%) as stressors among mining and construction workers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For physical health management, many prior studies focused on discussing the relationship between physical health and safety, including integrating safety and health performance into construction management [ 56 , 57 , 58 ], and analysing critical factors related to physical health on construction workplace safety management [ 7 , 30 , 59 ]. Therefore, many methods preventing construction worker injury incidents through the management of personal physical stress and organizational stressors are proposed, including reducing daily working hour and years, as well as improving rest time, sleeping time and the frequency of physical examination [ 60 , 61 , 62 , 63 , 64 ]. For mental health management, construction workers’ occupation and the surrounding context affecting their mental health could be grouped into four key themes: the importance of relationships, the impact of lifestyle, work characteristics, and mental health attitudes [ 53 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the mechanisms to face stressful events, adopted by construction workers, lead to worse feelings of psychological suffering (Langdon and Sawang 2017).…”
Section: Construction Workers' Well-beingmentioning
confidence: 99%
“…There are two particular coping styles in response to managing a stressful situation: problem-focused coping and emotion-focused coping (Langdon and Sawang 2017).The practice of meditation appears to be beneficial in environments where people have high levels of stress, such as the workplace (Cramer et al 2016;Elder 2014). During meditation, our experiences are not intentionally confronted, but only observed, and its practice turns into learning how not to be negatively influenced by understanding facts as mere mind flows (Teasdale 1999).…”
Section: Introductionmentioning
confidence: 99%